2003
DOI: 10.1080/00365540310000292
|View full text |Cite
|
Sign up to set email alerts
|

Isotype-specific Anti-38 and 27 kDa (mpt 51) Response in Pulmonary Tuberculosis with Human Immunodeficiency Virus Coinfection

Abstract: There is a need for rapid diagnostic methods to identify tuberculosis among human immunodeficiency virus-positive cases (HIV-TB). This study evaluated the serodiagnostic potential of the native 38 kDa and recombinant 27 kDa (mpt 51) antigens of Mycobacterium tuberculosis purified in the laboratory, when applied to HIV-TB patients. The antibody response was studied using enzyme-linked immunosorbent assays (ELISA). In the HIV-TB group, anti-38 kDa antibody of the immunoglobulin G (IgG), IgA and IgM isotypes was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 12 publications
3
19
0
Order By: Relevance
“…In sputum smear-negative patients, the sensitivity reported was lower (31%; 95% CI, 15 to 52). Specificities were 97% in both subgroups (15,18,59,69,76,77,102).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…In sputum smear-negative patients, the sensitivity reported was lower (31%; 95% CI, 15 to 52). Specificities were 97% in both subgroups (15,18,59,69,76,77,102).…”
Section: Resultsmentioning
confidence: 95%
“…A sufficient number of studies evaluating the performance of MPT51 were available to stratify the results by HIV infection status. In sputum smear-positive patients, MPT51 provided equivalent sensitivities in both HIV-negative TB patients (59%; 95% CI, 38 to 76) and HIV-positive TB patients (58%; 95% CI, 30 to 82); the specificities were 94% and 97%, respectively (10,69,85,108).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Importantly, MPT51 has been reported to be a potential marker for the diagnosis of TB, especially in AIDS patients. Ramalingam and colleagues (26) reported that early immune responses against 38-and 27-kDa (MPT51) proteins were detected in pulmonary TB patients, accompanied by human immunodeficiency virus coinfection. In addition, we demonstrated that MPT51 DNA vaccination using an attenuated Listeria carrier vaccination system induced protection against M. tuberculosis infection in mice (20).…”
Section: Discussionmentioning
confidence: 99%